The KONSEP KEADILAN PEREMPUAN DALAM ISLAM PERSPEKTIF ASGHAR ALI ENGINEER - Rauzatul Jannah; Umi Sumbulah (An Natiq, 2024)
The injustice of women is still rampant today. People often use religious teachings to perpetuate patriarchal systems. The purpose of this study is to examine the concept of women's justice in Islam from the perspective of Asghar Ali Engineer. This research uses qualitative methods with a library research approach, namely research conducted by reading the concept of equality of women used in the book "The Right of Women in Islam", data collection techniques in this study are carried out by reading, understanding, and examining parts of the book that are relevant to the theme of discussion, then content analysis is carried out to obtain a clear understanding of the information or data obtained. The result of this study is the concept of women's justice in Islam perspective Aghar Ali Engineer can be seen in his thoughts which are summarized on several themes, namely: Asghar criticism of women's justice, women's leadership, women's testimony, inheritance of women, women in marriage, and women and divorce. From these themes have shown about the various criticisms made by Asghar in order to defend women's justice, it can be understood that Asghar rejects various legal foundations that normatively degrade women.